Harmonization of Communication Channels: The Impact of IT Governance on Organizational Interactions - Harjono Padmono Putro (Sean Institute, 2022)
Harmonization of communication channels is a critical factor in achieving efficiency and effectiveness of internal communication in an organization. This research will explore how good IT governance can improve the overall harmonization of communication channels within an organization, as well as how this impacts interactions between organizational members. This research uses a qualitative approach with descriptive methods. The results of this research reveal that effective Information Technology (IT) governance contributes significantly to the harmonization ofcommunication channels within the organization. Good integration between various communication platforms, maintained information security, and flexibility in responding to changing communication needs are the main points that strengthen the effectiveness of organizational interactions. In addition, careful risk management and compliance with technology policies and regulations also support the continuity of communication channels, creating an environment that is safe, adaptive, and in accordance with applicable ethical and legal standards. The results of this research provide further insight into the important role of IT governance in forming a solid foundation for harmonious and effective internal communication.